PROFIL PUS MUDA USIA (15-19) DALAM KEIKUTSERTAAN PROGRAM KB, Di KAMPUNG KAYU GADANG TANGAH, NAGARI KOTO NAN TIGO UTARA SURANTIH, KECAMATAN SUTERA KABUPATEN PESISIR - Sisrinawati, Peni - (Pendidikan Sosiologi, 2014)
This study aimed to obtain information, analyze and discuss data on EFA Young Age (15-19) In the participation of family planning programs, in Kampung Kayu Tangah Tower, Nagari Koto Nan Tigo Surantih Northern, District Sutera South Coastal District. Marriage is a bond that acral and noble to regulate family life in order to establish a happy family based on one supreme divinity. In the village of Wood Tower Tangah pretty much going wedding Younger age and use of family planning after marriage because fear can not take care of the child, because of the economy and are on their own volition. The theory used in this study is the social action proposed by Max Weber selection of informants through purposive sampling of informants is withdrawal deliberately chosen by the researcher. Research methods of observation, interviews and documents. Data is tested using triangulation of data, the data were analyzed with an interactive model that consists of data reduction, data presentation and conclusion. The results of this study that addressed: 1. Knowledge pussy young age (15-19) about modern contraception and contraception is desired. 2. Peferensi gender and number of children desired by young pussy age (15-19). 3. Continuity Pus young (15-19) in the use of contraceptives.